2006
DOI: 10.1016/j.cattod.2006.01.036
|View full text |Cite
|
Sign up to set email alerts
|

In situ spectroscopic investigation of activation, start-up and deactivation of promoted sulfated zirconia catalysts

Abstract: Sulfated zirconia (SZ), unpromoted and promoted with 0.5-2.0 wt% Mn or Fe, was investigated by in situ IR and UV-vis spectroscopy during activation at 723-773 K and interaction with n-butane at 298-323 K. During start-up of the catalysts, the isomerization rate increases with the amount of water that is being formed, consistent with an activation of n-butane via oxidative dehydrogenation. Sulfate is the most likely oxidizing agent because activity is also observed for unpromoted SZ and without reduction of Mn.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 65 publications
(112 reference statements)
1
15
0
Order By: Relevance
“…Later, Klose et al also confirmed the formation and adsorption of water under isomerization reaction conditions by in situ IR investigations . Interestingly, they found that the isomerization rate was in direct proportion to the amount of water accumulated on the surface, which further confirmed the oxidative activation of alkane by sulfate species.…”
Section: Activation Of Alkane Over Sulfated Zirconiamentioning
confidence: 87%
See 3 more Smart Citations
“…Later, Klose et al also confirmed the formation and adsorption of water under isomerization reaction conditions by in situ IR investigations . Interestingly, they found that the isomerization rate was in direct proportion to the amount of water accumulated on the surface, which further confirmed the oxidative activation of alkane by sulfate species.…”
Section: Activation Of Alkane Over Sulfated Zirconiamentioning
confidence: 87%
“…Later, Klose et al also confirmed the formation and adsorption of water under isomerization reaction conditions by in situ IR investigations. 70 Interestingly, they found that the isomerization rate was in direct proportion to the amount of water accumulated on the surface, 6 which further confirmed the oxidative activation of alkane by sulfate species. Although the oxidative activation pathway can well explain the formation of carbenium ions in alkane isomerization over SZ catalyst, there are several questions still under debate.…”
Section: Development History Of Activation Pathwaymentioning
confidence: 88%
See 2 more Smart Citations
“…The observed variations in color from bluish to grayish indicate a change in the manganese valence, and shrinkage of the unit cell volume possibly indicates more oxygen vacancies. Manganese in these catalysts can be reduced during heating in inert gas [42,81]; it is thus conceivable that reduction takes place over months in the O 2 -depleted atmosphere of a glovebox. Activation was performed in inert gas so that a reduction would not be reversed.…”
Section: Catalytic Performance After Storagementioning
confidence: 99%